ZnO Nanostructures for Dye‐Sensitized Solar Cells Using the TEMPO+/TEMPO Redox Mediator and Ruthenium(II) Photosensitizers with 1, 2, 3‐Triazole‐Derived Ligands. Issue 12 (20th September 2016) - Wahyuono, Ruri Agung; Schulze, Benjamin; Rusu, Mihai; Wächtler, Maria; Dellith, Jan; Seyring, Martin; Rettenmayr, Markus; Plentz, Jonathan; Ignaszak, Anna; Schubert, Ulrich S.; Dietzek, Benjamin
Abstract: A series of thiocyanate‐free bis(tridentate) ruthenium(II) complexes incorporating 1, 2, 3‐triazole‐derived NNN‐, NCN‐, and CNC‐coordinating ligands has been employed for sensitizing ZnO photoanodes for dye‐sensitized solar cells (DSSCs). Additionally, the first use of the TEMPO + /TEMPO (2, 2, 6, 6‐tetramethyl‐piperidine‐1‐oxyl) redox mediator as a surrogate for the I3 − /I − redox couple in ZnO nanostructured DSSCs is presented. Compared with I3 − /I − ‐based electrolytes, shorter charge lifetimes and diffusion lengths were determined for the TEMPO + /TEMPO‐based electrolyte. Nonetheless, similar power conversion efficiencies (PCEs) were achieved with both electrolytes for the RuNCN and RuCNC complexes, whereas higher PCEs are enabled by the iodine‐free electrolyte in case of RuNNN. The combination of the molecular sensitizers and the TEMPO‐based electrolyte exhibits relatively high external quantum efficiency (EQE) and promising PCEs, ranging from 4.48 to 1.47 %, which are—in part—comparable to that of ZnO‐DSSCs with the benchmark N749 black dye. The TEMPO‐based electrolyte also exhibits less absorption compared with its I3 − /I − counterpart, a favorable feature for enhancing the light harvesting ability of the photoanode. Furthermore, the results show the effect of the dye‐sensitization procedure on the PCE values: The use of ethanol as the solvent compared with methanol increases the DSSC's efficiency, which is attributed to improved chemisorption of the sensitizer onto the ZnO surface. Abstract : Solar cells free from iodine and thiocyanate : TEMPO + /TEMPO electrolyte in combination with thiocyanate‐free Ru II complexes were investigated in ZnO‐based dye‐sensitized solar cells (DSSCs). DSSCs with bis(tridentate) Ru II complexes bearing 1, 2, 3‐triazole‐derived NNN‐, NCN‐, and CNC‐coordinating ligands (see figure) show promising power conversion and external quantum efficiencies comparable to DSSCs with iodine‐based electrolytes and thiocyanate‐based Ru II complexes.